(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper, a new fair certified email protocol is proposed. The proposed protocol uses offline trusted third party (TTP) that will only be involved if a party misbehaves, otherwise the TTP is inactive. The protocol is based on the verifiable and recoverable encryption of keys. In this regard, the recipient of an email will be able to verify if the encrypted key used to encrypt the email is correct. The protocol comprises of only three messages in the exchange sub-protocol and three messages in the recovery sub-protocol. The proposed protocol is more efficient compared with related protocols.